(untitled) (The Research of Medical Science Review, 2025)
Background: Chronic liver disease (CLD) refers to a long-term pathological process of continuous destruction of liver parenchyma and its gradual substitution with fibrous tissue, which eventually brings about Liver Cirrhosis related with a deadly result. CLDs have been long recognized and associated with depression Objectives: To assess the health-related quality of life among individuals receiving outpatient care for chronic liver disease. Method: A descriptive cross-sectional study conducted in in mayo hospital Lahore. Data is calculated from the 156 patients diagnosed with chronic liver disease with help of questionnaire. This data was analyzed by the help of frequency, percentage and chi square test with a significance less than 0.05. Results: Showed that 64.7% were females, with the majority 43.6% falling between 26 and 35 years, most 76.9% were married and resided in urban areas 50.6%. Educationally, a significant portion were able to read and write (35.3%). Most participants had an average quality of life score (55.8%), followed by those with good quality of life (42.3%) and a small percentage with poor quality of life (1.9%). Family income distribution showed that the majority50% fall within the range of 25,000 to 50,000 rupees. Conclusion: The findings indicated that the majority of patients experiencing an average quality of life were predominantly female and married. This study recommends the development of interventions customized to cater to the unique requirements of various demographic segments, including initiatives aimed at enhancing the quality of life for married individuals and addressing educational discrepancies among participants.